Viewing the COVID-19 Pandemic from Space: The Effect of COVID-related Mobility Declines on Night Light Brightness in Canada - Chan, Jeff (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2022)
High-frequency economic data for small areas is often difficult to obtain in Canada and other countries. This paper overcomes this limitation by using monthly data derived from satellite night light images as a proxy for economic activity in Canadian Census Divisions. This proxy is used in conjunction with Facebook mobility data to estimate the effects of mobility declines due to COVID-19 on economic activity. I find robust evidence that reductions in movements are strongly negatively associated with declines in luminosity. Further analyses suggest that this effect is weaker in more densely populated areas, but stronger in Census Divisions with a higher concentration of retail businesses. My findings suggest that policies which reduce the need for in-person activities can mitigate the negative effects of COVID-related mobility reductions on economic activity. This paper also further highlights the value of using monthly satellite night lights data in economic analysis.